A NEW APPROACH TO THE METHOD OF CARRYING OUT AEROBIC CLASSES WITH STUDENTS INSTITUTIONS OF HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2004)
The article is devoted to the new methods take lessons of aerobic with in higher educational institutions.